Assessment of four rounds of interlaboratory tests within the UNEP-coordinated POPs projects. (February 2022) - Fiedler, Heidelore; van der Veen, Ike; de Boer, Jacob
Abstract: Since 2005, the United Nations Environment Programme (UNEP) has supported developing countries with capacity building, including on-site training courses and provision on laboratory materials and consumables, and analysis of samples from Africa, Asia-Pacific and Latin America and the Caribbean (GRULAC) in designated expert laboratories. In order to check the performance of laboratories analyzing persistent organic pollutants (POPs) and giving trust into chemical analytical results, four rounds of interlaboratory assessments (ILs) were organized between 2010 and 2019. These were open to all POPs laboratories. In total, 41 575 z-scores, as indicators of performance, were generated in these four ILs; of these, 8 912 were from laboratories in countries supported by UNEP projects and 3 923 were from expert laboratories; these together constitute 31% of the total. 69% of all z-scores came from laboratories not participating in the UNEP projects, especially from China, who recognized the importance of such exercises for quality control at an early stage. The results showed that POPs analytical capacity has increased over the years, but some gaps could not be closed especially not when LC-MS/MS equipment is essential such as for PFAS and congener-specific HBCD. Use of mass spectrometers provides better results than ECD instruments due to the broad spectrum of organochlorine pesticides to be analyzed under the Stockholm Convention. The main conclusion for all laboratories is that interlaboratory assessments provide important and objective snapshots of performance for the laboratories themselves and for external clients. The methods used in any interlaboratory testing should be the same as during routine analysis between such tests. Graphical abstract: Image 1 Highlights: Africa for dl-POPs, PBDE, and PFAS lacks capacity; Latin American countries for PFAS and PBDE. Overall, performance for dl-POPs and to lesser extend PBDE and PFAS satisfactory. More than 60% of the z-scores for OCP and PCB were not satisfactory. Human milk and fish posed the biggest challenge to the laboratories. Regular – and successful – participation in interlaboratory assessments remains essential.